KRIOPRESERVASI TANAMAN PURWOCENG {Pimpinella pruatjan Molk.) DENGAN TEKNIK VITRIFIKASI - I Roostika; I Darwati; R Megia (BERITA BIOLOGI, 2007)
Pruatjan (Pimpinellapruatjan Molk.) is an Indonesian endangered medicinal plant that included in Appendix I based on CITES. Therefore it is a highly protected species. To avoid extinction of this plant, it is very important to conserve the plant. In vitro conservation is more suitable since this plant is difficult to be cultivated outside of its habitat. Cryopreservation technique may conserve this material for a long-term period. The objectives of this research were to find optimized treatments for pre culture, loading, and dehydration on cryopreservation of pruatjan. The research was conducted at Tissue Culture Laboratory in Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development, started from May to November 2007. Pre culture was conducted using DKW basal media that added by sucrose at the level of 0.3,0.4, and 0.5M for one and three days incubation. Loading was conducted in DKW basal media containing 2M glycerol and 0.4M sucrose for 15,30, and 45 minutes duration time. Dehydration was conducted in several cryoprotectants, namely PVS1 (22% glycerol + 13% propy lene glycol + 13% etylene glycol + 6% DMSO + 3% sucrose), PVS2 (30% glycerol + 15% etylene glycol + 15% DMSO + 0,4M sucrose), PVS3 (50% glycerol + 50% sucrose), and PVS4 (35% glycerol + 20% etylene glycol + sucrose 0.6M). Result showed that pruatjan could be preserved through cryopreservation by vitrification method. The best pre culture was using 0.3 M sucrose for one day, the best loading was 30 minutes, while the best cryoprotectant was PVS2 with 90% success before freezing and 40% after freezing. The success may be improved by applying pre growth treatment, optimizing temperature of thawing, modification of recovery media and incubation condition.